The Influence of Study Time, School Rules, Curiosity, Family Social Interaction, and Learning Facilities on the Learning Outcomes of Class X Students in Economics Subjects - Nur Ida Fatini; Jimi Ronald; Mona Amelia (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of study time, school rules, curiosity, family social interaction, and learning facilities on the learning outcomes of tenth-grade students in Economics subjects at SMAN 16 Padang. This research employed a quantitative approach with a survey method using questionnaires. The population consisted of 120 students, and the sampling technique applied was total sampling. Data analysis was conducted using multiple linear regression. The results showed that all five independent variables (study time, school rules, curiosity, family social interaction, and learning facilities) significantly influenced students’ learning outcomes, both partially and simultaneously. This was evidenced by the significance values of each variable (sig < 0.05) and the F-test result of 361.327 with sig 0.000 < 0.05. Therefore, it can be concluded that these internal and external factors play an important role in improving students’ learning outcomes.